Caring for people with spastic paraparesis: rehabilitation nursing interventions for daily activities (Research, Society and Development, 2020)
Objective: To describe the implications of short, medium and long-term, institutional and home care for people with traumatic brain injury and dependence for daily activities. Method: Experience report on care planning and nursing care for people with severe spastic paraparesis. Results: It made it possible to share learning with undergraduate and graduate students in nursing, understanding that the rehabilitating nurse effectively plays a decisive role in the implementation of care strategies focused on the functional gains of people with self-care deficit, because it is the professional who assists them in the day-to-day physical rehabilitation. Final considerations: The rehabilitation nurse's interventions should consider the confrontations of the person with acquired disability starting from the impact or denial phase, in the hospital space and total dependence for basic nursing care, until reaching the reconstruction phase, focusing on social inclusion and promotion of the client's functional autonomy for self-care.